Higher education in Brazil: the resistance of philanthropy to guarantee universal access to the university - Fossatti, Paulo; Jung, Hildegard Susana (Universidade Estadual de Campinas, 2017)
The experience report recovers the struggle for the maintenance of Philanthropy in Brazil, through a Pension Reform, which guarantees access to more than 600 thousand students of Basic Education and Higher Education, totally free, in public community education institutions. The aim is to make the reader aware of the need to build a policy of cooperation between state public and private public Higher Education Institutions (HEI) as a strategy for the access and permanence of impoverished young people in higher education. This is the story of the experiences of the authors and their partner institutions in the fight for the maintenance of Philanthropy as a device to guarantee the access and permanence of more young people in higher education. The report is accompanied by documentary data and field journal of researchers in their actions with society, government, and educational entities. As Learning evidences: the lack of knowledge of the government, parliamentarians, and society on the subject; The reductionism of the concept of what is public; The resistance of associations and people for philanthropic reasons and a political mobilization of philanthropic entities in the sensitization of parliamentarians for a new concept of public service. It is concluded by resistance and vigilancein the maintenance of several devices to guarantee philanthropy as a form of access to Higher Education, especially the poor young people.